SOPHIOLOGICAL ASPECT DOGMA WORSHIP OF ICON IN SERGIUSBULGAKOV’S CONCEPTION - Галуйко, Р. М. (Proceedings of the National Aviation University Series Philosophy Cultural, 2015)
The article researches basic principles of the sophiological conceptions of icons by SergiusBulgakov, priest and philosopher.